Kajian Undang-Undang Perlindungan Konsumen dalam Perspektif Hukum Islam - Yusri, Muhammad (Universitas Muhammadiyah Surabaya, 2019)
The birth of Consumerism Protection Law (UUPK) is meanthas a porpuse to protect consumer in every business activity from many deceitfull whom did by producers and other businessmen. The moslem jurists were admitted that in UUPK have been containing the business ethics substantions that are appropriate with spirit in Islamic teachings. However, as a human law product, UUPK is not loose from some deficits. The deficits will appear clearly when several paragraphs in UUPK compared with philosophical principles in Islamic law. And, this research intended to see how far relevance UUPK towards the maslahat's spirit in Islamic law.Â Key Word : UUPK, Etika Bisnis Islam, Maslahat.